Methane emissions generated by urban solid waste disposal: the case of Tuxtla Gutiérrez, Chiapas, México - Díaz Nigenda, Emmanuel; Venegas-Sandoval, Andrea; Vázquez-Morales, Williams; Nájera-Aguilar, Hugo Alejandro; Morales-Iglesias, Horacio; Vázquez Ovando, Cecilia (Acta Universitaria, 2022)
Municipal solid waste (MSW) is an environmental problem affecting cities around the world, its management is vital to minimize impacts such as the emission of greenhouse gases (GHG). Taking Tuxtla Gutiérrez as a case study, the methane (CH4) emissions generated by the disposal of MSW were quantified for the period 2000-2020 by applying the default method of 1996 IPCC guidelines. It was necessary to calculate the amount of waste generated annually from the size of the population and per capita daily MSW generation (PCG). The emissions increased from 5857.03 t CH4 in 2000 to 14 734.24 t CH4 in 2020, with growth rates ranging between 1.19% and 29.3% and an annual average of 4.89%. The magnitude of emissions exceeds those generated in cities with a greater socio-economic development and evinces the problems shared by several cities in Mexico.